Inventory of the Archive of Legal protocol of the Merindad of Tudela: revision and updating I: notaries of Tudela - Pérez Ochoa, Íñigo; Roce Martínez, Jesús (Huarte de San Juan. Geografía e Historia, 2011)
25 years after the inventory of the Archives’contents of Tudela’s merindad, it was necessary to do an updating, presenting a descriptive and precise instrument and increased thanks for the helping of new technologies. During the period since then, a constant revision has been achieved, reinforced by the treatment and digitalization of Documentation corresponding to the Notary’s office of Tudela since the XIV to the XVI. As a result, after an introducing, where a briefly procedure has been submitted for the appointment of the notaries, An aplicable legislation to keep the notarial documents, the preservation of the list of titles in different places, the organisation and description, we present the inventory of the notarial Documents corresponding to Tudela’s Notaries and of the deed’s indexes of all the Merindad.